Lumberjanes (2014), issue 27 ebook - Watters, Shannon (Lumberjanes (2014)., 2018)
The Lumberjanes and Barney try to figure out how to woo giant mystical birds, while the Zodiac cabin has some things to say to the Roanokes about their friend Diane, who they miss dearly.